2021
DOI: 10.3390/jof7060409
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptional Response of Aspergillus niger to Blocked Active Citrate Export through Deletion of the Exporter Gene

Abstract: Aspergillus niger is the major industrial citrate producer worldwide. Export as well as uptake of citric acid are believed to occur by active, proton-dependent, symport systems. Both are major bottlenecks for industrial citrate production. Therefore, we assessed the consequences of deleting the citT gene encoding the A. niger citrate exporter, effectively blocking active citrate export. We followed the consumption of glucose and citrate as carbon sources, monitored the secretion of organic acids and carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…We observed that CexA overexpression dramatically influenced the transcriptional pattern of genes involved in carbohydrate transport and metabolism ( Figure S4 ), suggesting its impacts on carbon metabolic flux redistribution. Three glucose transporters MstC, MstG, and MstH displayed the similar expression pattern as the cexA gene, which was consistent with the previous transcriptional analysis [ 47 ]. Additionally, we also discovered that several genes beneficial for intracellular citric acid accumulation were significantly regulated, including starch hydrolysis, precursor supply, mitochondrial citrate/malate shuttle, alternative oxidase respiratory chain, citric acid degradation, and by-product biosynthesis.…”
Section: Discussionsupporting
confidence: 90%
“…We observed that CexA overexpression dramatically influenced the transcriptional pattern of genes involved in carbohydrate transport and metabolism ( Figure S4 ), suggesting its impacts on carbon metabolic flux redistribution. Three glucose transporters MstC, MstG, and MstH displayed the similar expression pattern as the cexA gene, which was consistent with the previous transcriptional analysis [ 47 ]. Additionally, we also discovered that several genes beneficial for intracellular citric acid accumulation were significantly regulated, including starch hydrolysis, precursor supply, mitochondrial citrate/malate shuttle, alternative oxidase respiratory chain, citric acid degradation, and by-product biosynthesis.…”
Section: Discussionsupporting
confidence: 90%
“…Shi et al 102 stated that increasing fungal biomass during fermentation resulted in increasing the protein content of the end products. The ability of microorganisms to secrete a variety of enzymes, 103 biotransformation of soluble carbohydrate into microbial protein, 104 secretion of some extracellular components, 105 and free hydrolyzed peptides that are proteinaceous in nature, 106 might result in an increase in protein content during fermentation. In addition, increasing non‐proteinaceous substances like chitin which is rich in the fungal cell walls and nucleic acids on account of fungal proliferation could also help to boost the protein content 107 .…”
Section: Beneficial Effects Of a Nigermentioning
confidence: 99%
“…Likewise, several positive reports on genetic engineering of A. niger have recently been reported. 103,171 The great potential of genome editing and engineering should also be exploited to reduce the challenges related to limiting the utilization of A. niger in the future, which will help to sustain the shrimp aquaculture with increased economic benefits.…”
Section: Genetic Engineeringmentioning
confidence: 99%
“…Aspergillus niger is a powerful cell factory and among others, is efficiently used to produce organic acids such as citric-, oxalic-and gluconic acid (2,3). Citric-and oxalic acid are intracellularly produced and actively secreted (4)(5)(6)(7). In contrast, gluconic acid is the product of an extracellular conversion of glucose in a collaboration of three extracellular enzymes: glucose oxidase (GOx), lactonase and catalase (8).…”
mentioning
confidence: 99%
“…FIG6 Expression analysis of A. niger wildtype and AQP knock-out strains under hydrogen peroxide inducing conditions. Results of strain N402 (A), ΔaqpD (B), ΔaqpE (C) and ΔaqpF (D).…”
mentioning
confidence: 99%